A Look to the Interior: Trends in U.S. Immigration Removals by Criminal Conviction Type, Gender, and Region of Origin, Fiscal Years 2003-2015. (August 2019) - Moinester, Margot
Over the past two decades, the U.S. federal government has sought to increase its capacity to find, apprehend, and deport noncitizens residing in the United States who have violated federal immigration laws. One way the federal government has done this is by partnering with state and local law enforcement agencies on immigration enforcement efforts. The present study analyzes the records of all 1, 964, 756 interior removals between fiscal years 2003 and 2015 to examine how, if at all, the types of criminal convictions leading to removal from the U.S. interior have changed during this period of heightened coordination between law enforcement agencies and whether there are differences by gender and region of origin in the types of convictions leading to removal. Findings show that as coordination between law enforcement agencies intensified, the proportion of individuals removed from the U.S. interior with either no criminal convictions or with a driving-related conviction as their most serious conviction increased. Findings also show that the proportion of individuals removed with no criminal convictions was greater for women than for men and that the share of individuals removed with a driving-related conviction as their most serious conviction was greater for Latin Americans than for individuals from all other regions. Given renewed investment in these types of law enforcement partnerships under the Trump administration, the patterns presented in this article may foreshadow trends to come.